A cognitive stylistic of Taylor Swift’s song 'I can do it with a broken heart' - Miqdad Zephanda; Fazal Hariski Nasution; Muhammad Shofi Nasution; Lailan Haz Anugrahyuni Siregar; Rahmadsyah Rangkuti (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study analyzes the lyrics of Taylor Swift's song 'I Can Do It With A Broken Heart' to explore how she conveys themes of resilience and emotional turmoil. The research addresses the gap in understanding the specific mechanisms through which contemporary music reflects complex emotional states. Utilizing qualitative text analysis, the study examines the song's interpersonal dynamics, framing, and metaphors. Findings reveal a tension between the protagonist's public persona and private pain, highlighted through vivid metaphors and imagery that depict resilience despite adversity. This analysis contributes to the broader discourse on music as a form of emotional expression, emphasizing its societal implications.